Rio+20 realpolitik and its implications for "The future we want" - Marianne Beisheim; Birgit Lode; Nils Simon (Stiftung Wissenschaft und Politik (SWP), 2012)
The United Nations Conference on Sustainable Development (UNCSD, or Rio+20) took place in Rio de Janeiro, Brazil, June 20-22, 2012. While the outcome document of the conference responded to most of the demands of the developing and emerging nations gathered in the Group of 77 (G-77), the European Union and many non-governmental organizations criticized the reform proposals for not going far enough and being too vague. In a surprising act of pragmatic Realpolitik, host country Brazil had proposed the compromise text shortly before the beginning of the conference, and then managed to push it through almost unaltered-and thus succeeded in reaching an agreement in Rio, despite the difficult pre-negotiations. The outcome document, 'The Future We Want,' however, reflects only a lowest common denominator of the community of states on international sustainability policy. Germany and the European Union should now strive to reach beyond these meager results in the upcoming post-Rio processes
Keywords: 320